Identifying Factors Most Important to Lower Extremity Trauma Patients: Key Concepts from the Development of a Patient-Reported Outcome Instrument for Lower Extremity Trauma, The LIMB-Q. Issue 5 (May 2020) - Mundy, Lily R.; Klassen, Anne; Grier, A. Jordan; Gibbons, Christopher; Lane, Whitney; Carty, Matthew J.; Pusic, Andrea L.; Hollenbeck, Scott T.; Gage, Mark J.
Abstract : Background: Severe lower extremity injuries are challenging to treat. The aspects of limb salvage and amputation most important to patients are not well-defined. This study's aim is to develop a conceptual framework for a patient-reported outcome instrument for lower extremity trauma patients, by defining issues and concepts most important to this patient population. Methods: This is an interpretative description of transcripts collected from semistructured qualitative interviews at a single institution. High-energy lower extremity trauma patients were recruited by means of purposeful sampling to maximize variability. Thirty-three participant interviews were needed to reach content saturation. These participants were aged 19 to 79 years; 21 were men (63.6 percent); participation was after reconstruction [ n = 15 (45.5 percent)], after amputation [ n = 11 (33.3 percent)], or after amputation after failed reconstruction [ n = 7 (21.2 percent)]. Interviews were recorded, transcribed, and coded line-by-line. Concepts were labeled with major and minor themes and refined through a process of constant comparison. Analysis led to the development of a conceptual framework and item pool to inform the development of a patient-reported outcome measure. Results: In total, 2430 unique codes were identified and used to generate the conceptual framework covering 10 major themes: appearance, environment, finances, physical, process of care, prosthesis, psychological, sexual, social, and treatment. Conclusions: This study establishes a comprehensive set of concepts, identifying what is most important to severe lower extremity trauma patients. These findings can be used to inform and focus research and clinical care, and provides the framework to develop a lower extremity trauma-specific patient-reported outcome instrument: the LIMB-Q.